2011
DOI: 10.1007/s11240-011-9978-7
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis and organogenesis in apomictic and sexual Brachiaria brizantha

Abstract: Brachiaria brizantha (syn. Urochloa brizantha) is an important tropical forage grass widely cultivated in Brazil. In order to optimize tissue culture conditions for B. brizantha, in vitro culture of mature seeds, basal segments and leaf segments from in vitro plants of an apomictic and a sexual genotype of B. brizantha was performed. When cultured on different media, leaf segments yielded nonembryogenic calluses which formed several roots. Friable calluses from mature seeds and basal segments explants incubate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 48 publications
5
19
0
8
Order By: Relevance
“…1A). These results are in accordance with previous observations showing high efficiency of the M1.3/MS3 media combination for inducing and regenerating plants via somatic embryogenesis in B. brizantha (Cabral et al 2011). The profuse development of roots, regardless of the induction medium, was more frequent in NBreg than in MS3 medium (Fig.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…1A). These results are in accordance with previous observations showing high efficiency of the M1.3/MS3 media combination for inducing and regenerating plants via somatic embryogenesis in B. brizantha (Cabral et al 2011). The profuse development of roots, regardless of the induction medium, was more frequent in NBreg than in MS3 medium (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Similar behavior was observed in bud formation in Brachiaria spp. on micropropagation medium (Cabral et al 2011). The induction/regeneration media combination NB/NBreg was originally used for rice somatic embryogenesis (Sallaud et al 2003), and even though these media are richer in free amino acids than M1.3/MS3, the best response for B. brizantha was obtained with the M1.3/MS3…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike some direct plant regeneration systems (without a callusing stage) using the shoot apices as explants, we found in our preliminary studies that the white basal parts of newly germinated seedlings of 'Alamo' were readily available and had high capability of producing regenerable calluses. Similar results have recently been reported on signalgrass (Brachia brizantha), for which highly regenerable calluses were induced from mature seeds as well as basal segments of in vitro seedlings (Cabral et al 2011). Additionally, switchgrass seedlings have been reported to be susceptible to the infection of A. tumefaciens strains (Chen et al 2010).…”
Section: Introductionsupporting
confidence: 83%
“…Some studies have demonstrated that 2,4-D and BA also induce the somatic embryogenesis, e.g. in Brachiaria brizantha cultures (Cabral et al 2011).…”
Section: Resultsmentioning
confidence: 99%